2011
DOI: 10.4049/jimmunol.1002485
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticosteroids Modify Langerhans Cells To Produce TGF-β and Expand Regulatory T Cells

Abstract: Although glucocorticosteroids (GCSs) have been used for many decades in transplantation and (auto)inflammatory diseases, the exact mechanisms responsible for their immunosuppressive properties are not fully understood. The purpose of this study was to characterize the effects of oral GCSs on the cutaneous immune response. We analyzed, by immunofluorescence staining and quantitative RT-PCR, residual skin biopsy material from a clinical study in which we had used oral GCS as positive control for determining the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 71 publications
1
63
0
3
Order By: Relevance
“…Consistent with the results of our study, Lebre et al (20) found that CD1c+ DCs exhibit aberrant functions in AD patients because these cells could not induce a Th1 immune response, even in the presence of a strong Th1 stimulus. Due to the prevalent initiator but complex nature of mDCs in the skin's immune system, many therapeutic approaches target these cells via modifications of their function or the surrounding tissue microenvironment, that is, topical treatment of AD with calcineurin inhibitors and corticosteroids (21,22). Therefore, it is important to develop methods that are suitable for the investigation of the direct effects of newly developed therapies on DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the results of our study, Lebre et al (20) found that CD1c+ DCs exhibit aberrant functions in AD patients because these cells could not induce a Th1 immune response, even in the presence of a strong Th1 stimulus. Due to the prevalent initiator but complex nature of mDCs in the skin's immune system, many therapeutic approaches target these cells via modifications of their function or the surrounding tissue microenvironment, that is, topical treatment of AD with calcineurin inhibitors and corticosteroids (21,22). Therefore, it is important to develop methods that are suitable for the investigation of the direct effects of newly developed therapies on DCs.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments, we also observed that unstimulated mDCs had a similar capacity to polarise Th1 cells in atopic and non-atopic individuals; however, this ability of atopic mDCs became impaired after stimulation. Consistent with the results of our study, Lebre et al (20) found that CD1c+ DCs exhibit aberrant functions in AD patients because these cells could not induce a Th1 immune response, even in the presence of a strong Th1 stimulus.Due to the prevalent initiator but complex nature of mDCs in the skin's immune system, many therapeutic approaches target these cells via modifications of their function or the surrounding tissue microenvironment, that is, topical treatment of AD with calcineurin inhibitors and corticosteroids (21,22). Therefore, it is important to develop methods that are suitable for the investigation of the direct effects of newly developed therapies on DCs.…”
mentioning
confidence: 99%
“…Due to the prevalent initiator but complex nature of mDCs in the skin's immune system, many therapeutic approaches target these cells via modifications of their function or the surrounding tissue microenvironment, that is, topical treatment of AD with calcineurin inhibitors and corticosteroids (21,22). Therefore, it is important to develop methods that are suitable for the investigation of the direct effects of newly developed therapies on DCs.…”
mentioning
confidence: 99%
“…GCs are responsible for reducing the resistance of wild animals to viruses and increase their tolerance to harbouring the virus in a minimal range without causing any disease [15]. The possibility has been suggested that by activating organ-specific regulatory mechanisms GCs also influence the host-pathogen interaction [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…When challenged by chronic anthropogenic stressors, immunologically suppressed rodents express elevated levels of GCs which mediate an organ-specific regulation that supports tolerance while removing resistance to hantavirus infection [15]. GCs block inflammatory pathways and induce apoptosis mediated by T reg lymphocytes [17,105,106,107]. GCs not only suppress differentiation of DC but also induce production of tolerogenic DC which express elevated IL-10 and TGF-β.…”
mentioning
confidence: 99%